2022
DOI: 10.7554/elife.82709
|View full text |Cite
|
Sign up to set email alerts
|

Two neuronal peptides encoded from a single transcript regulate mitochondrial complex III in Drosophila

Abstract: Naturally produced peptides (<100 amino acids) are important regulators of physiology, development, and metabolism. Recent studies have predicted that thousands of peptides may be translated from transcripts containing small open reading frames (smORFs). Here, we describe two peptides in Drosophila encoded by conserved smORFs, Sloth1 and Sloth2. These peptides are translated from the same bicistronic transcript and share sequence similarities, suggesting that they encode paralogs. Yet, Sloth1 and Sloth2 are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 86 publications
(117 reference statements)
2
1
0
Order By: Relevance
“…Interestingly, 40% of smORF peptides display a motif, that could be useful to address its biological function. More than 10% of smORF peptides appear to be addressed to mitochondria, suggesting a tendency of the smORF peptides to localise to this organelle compared to the whole proteome (6%) as previously observed (Bosch et al, 2022; van Heesch et al, 2019). Furthermore, the phenotypes obtained are diverse, affecting cell survival, segment fusion or tissue growth, suggesting that smORF peptides are involved in all cellular processes.…”
Section: Discussionsupporting
confidence: 70%
“…Interestingly, 40% of smORF peptides display a motif, that could be useful to address its biological function. More than 10% of smORF peptides appear to be addressed to mitochondria, suggesting a tendency of the smORF peptides to localise to this organelle compared to the whole proteome (6%) as previously observed (Bosch et al, 2022; van Heesch et al, 2019). Furthermore, the phenotypes obtained are diverse, affecting cell survival, segment fusion or tissue growth, suggesting that smORF peptides are involved in all cellular processes.…”
Section: Discussionsupporting
confidence: 70%
“…Interestingly, 40% of smORF peptides display a motif, that could be useful to address its biological function. More than 10% of smORF peptides appear to be addressed to mitochondria, suggesting a tendency of the smORF peptides to localize to this organelle compared to the whole proteome (6%) as previously observed [43,44]. Furthermore, the phenotypes obtained are diverse, affecting cell survival, segment fusion or tissue growth, suggesting that smORF peptides are involved in all cellular processes.…”
Section: Smorf Peptides Provide a Pool Of Novel Developmental Actorssupporting
confidence: 55%
“…These studies and others have identified smaller proteins (often defined as less than 100 amino acids) called micropeptides or small Open Reading Frames (smORFs), that localize inside mitochondria (Tharakan and Sawa, 2021;Zheng and Xiang, 2022). In metazoans, these internal mitochondrial micropeptides have been frequently implicated in critical functions such as the assembly of respiratory complexes (Bosch et al, 2022;Chu et al, 2019;Rathore et al, 2018;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%